Dosimetry of X-ray and gamma irradiation using gafchromic EBT film; Modern technique and technologies MTT' 2012 - Suhkikh Y. S. (Section VIII: Modern Physical Methods in Science, Engineering and Medicine, 2012)
Заглавие с титульного листа